Construction of high electrical conductive nickel phosphide alloys with controllable crystalline phase for advanced energy storage. (1st April 2017) - Liu, Mao-Cheng; Hu, Yu-Mei; An, Wen-Ya; Hu, Yu-Xia; Niu, Leng-Yuan; Kong, Ling-Bin; Kang, Long
Graphical abstract: High electrical conductive Ni-P alloys are fabricated through liquid phase method. They deliver high specific capacity and excellent rate capability. Highlights: Nickel phosphides with controllable crystalline phase were fabricated by liquid phase method. They showed high electrical conductivity and excellent electrochemical performance. Asymmetric supercapacitors were assembled and exhibited high energy density and long lifespan. Abstract: Nickel–based compounds are promising energy storage materials due to their high specific capacitance and energy density, but their practical applications are severely prevented by the poor rate capability which ascribed to the low conductivity. Herein controllable synthesis of high electrical conductive nickel phosphide alloys is achieved by conversion of Ni3 C into Ni2 P, Ni7 P3 and Ni12 P5 using trioctylphosphine as phosphorus source. The current-voltage curves indicating that the conductivity of these nickel phosphide alloys is higher than commercial graphite. They deliver excellent electrochemical characteristics including high specific capacitance and excellent rate capability. Simultaneously, the asymmetric supercapacitors with high energy density and long cycle life are also assembled based on nickel phosphide alloys as positive electrode and activated carbon as negative electrode. The AC//Ni2 P asymmetric supercapacitor delivers the highest specific capacity of 239.5C g −1 at a current density of 0.5 A g −1 and a maximum energy density of 53.2 Wh kg −1 (at a power density of 0.3998 kW kg −1 ). The study will provide a new strategy for the construction of high performance energy storage materials by enhancing their intrinsic electrical conductivity and controlling their microstructure.